Fitocistatinas: caracterização bioquímica e aplicação na transformação genética de cana-de-açúcar - Schneider, Vanessa Karine (Universidade Federal de São Carlos, 2018)
Cystatins are tight-binding, competitive cysteine-peptidase inhibitors. In plants, these proteins are part of natural defense mechanism, regulating endogenous and exogenous peptidases. In humans, cystatins are responsible for regulation of physiological processes, which are limited by overexpression of cysteine peptidases. The lack of regulation of biological mechanisms that control activity of cathepsin-like cysteine peptidases result in several diseases such as cancer, osteoporosis, obesity and cardiovascular diseases. Several studies have evaluated the potential of cystatins in inhibition of human cathepsins for disease regression. In addition to biotechnological application in health area, cystatins have been widely used in studies aimed at the control of insect pests in agriculture. Insects of Hemiptera, Coleoptera and Homoptera orders have cysteine-peptidases as digestive enzymes. Overexpression of cystatins in transgenic plants has been performed in a large number of species, and results are promising, with interference in mortality, reproduction and development of insects fed with these plants. In this way, this work is divided in two chapters aiming at biotechnological application of phytocystatins in agriculture through the genetic transformation of sugarcane with a cystatin (CaneCPI-4) aiming at resistance to Migdolus fryanus insect (Chapter 1) and biotechnological application of phytocystatins in human health through characterization of Citrus cystatins and inhibition studies with human cathepsins and cysteine-peptidases from different organisms (Chapter 2). Chapter 1 corresponds to experiments of genetic transformation of sugarcane with cystatin CaneCPI-4 by methods of biolistics and Agrobacterium tumefaciens. Transformations made by biolistics resulted in few transforming events, due to low plant regeneration efficiency. In sugarcane genetic transformation using Agrobacterium tumefaciens it was possible to observe that regeneration of transformed plants showed to be more efficient than the regeneration of plants transformed by biolistics, being healthier, with greater number of events and good plant development, accounting for 92 plants under development. Chapter 2 corresponds to characterization of five Citrus cystatins, CsinCPI-1, CsinCPI-2, CclemCPI-1, CclemCPI-2 and CclemCPI-3 by cloning into pET28a expression vector, expression in Escherichia coli cells, protein purification by affinity chromatography and cysteine-peptidase inhibition assays. Cystatin CclemCPI-3 is bifunctional, being able to inhibit activity of a legumain and enzymes of papain family. The activity of cysteine-peptidase papain was efficiently inhibited by all cystatin tested, with Ki on the order of nanomolar. Human cathepsin S was efficiently inhibited by CsinCPI-2 (Ki = 0.11 nM). Cathepsins K and L are efficiently inhibited by CclemCPI-2 (Ki = 0.00098 nM and 0.00608 nM, respectively). Cathepsin B is efficiently inhibited by CclemCPI-1 (Ki = 0.42 nM). These results are promising for future trials evaluating effect of cystatin in vivo, which may result in biotechnological application of Citrus cystatins in human disease control.
Phytocystatins: biochemistry characterization and application in sugarcane genetic transformation
Keywords: Cistatina; Cana-de-açúcar; Citrus; Cisteíno-peptidase; Inibidor; CIENCIAS BIOLOGICAS::BIOQUIMICA